Intestinal bacterial indicator phylotypes associate with impaired DNA double-stranded break sensors but augmented skeletal bone micro-structure. (16th December 2019) - Maier, Irene; Liu, Jared; Ruegger, Paul M; Deutschmann, Julia; Patsch, Janina M; Helbich, Thomas H; Borneman, James; Schiestl, Robert H
Abstract: Intestinal microbiota are considered a sensor for molecular pathways, which orchestrate energy balance, immune responses, and cell regeneration. We previously reported that microbiota restriction promoted higher levels of systemic radiation-induced genotoxicity, proliferative lymphocyte activation, and apoptotic polarization of metabolic pathways. Restricted intestinal microbiota (RM) that harbors increased abundance of Lactobacillus johnsonii (LBJ) has been investigated for bacterial communities that correlated radiation-induced genotoxicity. Indicator phylotypes were more abundant in RM mice and increased in prevalence after whole body irradiation in conventional microbiota (CM) mice, while none of the same ten most abundant phylotypes were different in abundance between CM mice before and after heavy ion irradiation. Muribaculum intestinale was detected highest in female small intestines in RM mice, which were lacking Ureaplasma felinum compared with males, and thus these bacteria could be contributing to the differential amounts of radiation-induced systemic genotoxicity between the CM and RM groups. Helicobacter rodentium and M.intestinale were found in colons in the radiation-resistant CM phenotype. While the expression of interferon-γ was elevated in the small intestine, and lower in blood in CM mice, high-linear energy transfer radiation reduced transforming growth factor-β with peripheral interleukin (IL)-17 in RM mice, particularly in females. We found that female RM mice showed improved micro-architectural bone structure and anti-inflammatory radiation response compared with CM mice at a delayed phase 6 weeks postexposure to particle radiation. However, microbiota restriction reduced inflammatory markers of tumor necrosis factor in marrow, when IL-17 was reduced by intraperitoneal injection of IL-17 neutralizing antibody.